Answer:
y is equal to 1.5, and x is equal to -4
Step-by-step explanation:
given:
![4x + 8y = -4](https://tex.z-dn.net/?f=4x%20%2B%208y%20%3D%20-4)
![2y - 5x = 23](https://tex.z-dn.net/?f=2y%20-%205x%20%3D%2023)
We can start by factoring 4 out of the first equation:
![x + 2y = -1](https://tex.z-dn.net/?f=x%20%2B%202y%20%3D%20-1)
Now let's multiply it by -5:
![-5x - 10y = 5](https://tex.z-dn.net/?f=-5x%20-%2010y%20%3D%205)
We'll rearrange the other equation to match that (just for clarity):
![-5x + 2y = 23](https://tex.z-dn.net/?f=-5x%20%2B%202y%20%3D%2023)
Now let's subtract the modified equation from that:
![\begin{array}{c}-5x + 2y = 23\\-5x - 10y = 5\\ \ \ \ \ \ \ \ \ \ \ 12y = 18\end{array}](https://tex.z-dn.net/?f=%5Cbegin%7Barray%7D%7Bc%7D-5x%20%2B%202y%20%3D%2023%5C%5C-5x%20-%2010y%20%3D%205%5C%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%20%5C%2012y%20%3D%2018%5Cend%7Barray%7D)
So y is equal to 18/12, or 1.5
Let's plug that into one of the first equations and see what we get:
![2y - 5x = 23\\2(1.5) - 5x = 23\\3 - 5x = 23\\-5x = 20\\x = -4](https://tex.z-dn.net/?f=2y%20-%205x%20%3D%2023%5C%5C2%281.5%29%20-%205x%20%3D%2023%5C%5C3%20-%205x%20%3D%2023%5C%5C-5x%20%3D%2020%5C%5Cx%20%3D%20-4)
Giving us an x value of negative four. Let's plug that into the other equation to confirm:
![4x + 8y = -4\\4(-4) + 8y = -4\\-16 + 8y = -4\\-4 + 2y = -1\\2y = 3\\y = 1.5](https://tex.z-dn.net/?f=4x%20%2B%208y%20%3D%20-4%5C%5C4%28-4%29%20%2B%208y%20%3D%20-4%5C%5C-16%20%2B%208y%20%3D%20-4%5C%5C-4%20%2B%202y%20%3D%20-1%5C%5C2y%20%3D%203%5C%5Cy%20%3D%201.5)
That matches up, so our answer is correct.